The Long Arm of an Unsupportive Work-Family Culture in Work Organizations: Crossover to the Partner's Work-Family Balance Satisfaction in Dual-Earner Couples - Janine Bernhardt; Mareike Bünning (Applied Research in Quality of Life, 2022)
This study analyzes how an unsupportive organizational work-family culture experienced by one employed parent at work can cross over to their partner and reduce the latter's satisfaction with work-family balance (WFBS). Workplace cultures that are structured around the “ideal worker” norm have enormous and often detrimental impacts on parents' abilities to manage work and family roles. Drawing on crossover theory, we argue that these kinds of unsupportive work-family cultures have adverse consequences, not only for working parents but also for their partners. We hypothesize that if one partner experiences an unsupportive work-family culture, they can provide less instrumental and emotional support to the other partner, which reduces the other partner's WFBS. We use a unique dataset of 556 dual-earner couples with young children surveyed in Germany in 2015 and perform multivariate regression analysis and structural equation modelling. We find robust evidence that mothers were less satisfied with work-family balance if fathers reported an unsupportive work-family culture in their organization. There was only weak evidence, however, for crossover between an unsupportive work-family culture at the mother's workplace and the father's WFBS. Mediation analysis suggests that these associations were transmitted in part through reduced emotional support, whereas instrumental support did not appear to play a role. The findings lend support to the argument that an unsupportive work-family culture in one parent's workplace reduces the emotional support they provide to their partner, which reduces the partner's WFBS.
doi:10.7802/2039
Keywords: 300; work-family balance satisfaction; organizational work-family culture; ideal worker norm; crossover; social support